UTILIZING MARKET ANALYSIS TO INCREASE COMPETITIVE ADVANTAGE - Ian Zulfikar (Sean Institute, 2023)
Because of the intense competition that exists in the business world, every organization must contend with a wide variety of opportunities and threats, both from within the country and from beyond it. Businesses are obligated to constantly be aware of and comprehend what developments are taking place in the market as well as the requirements of their customers. As a result, businesses have the opportunity to benefit from previously conducted market research. In order to gain a competitive advantage in the market, it is critical to conduct market study, as this article explains. In this study, a descriptive qualitative approach was taken to data collection, with literature review serving as the primary source of information. The author of this article discusses market analysis, competitive advantage, and how to utilize market analysis to determine customer preferences, market trends, and rivals while also adapting business tactics to attain a company's competitive edge in the market.